PENGARUH VOLUME AIR TANAH TERHADAP DAYA SERAP SISTEM FAS (FILTRASI, ABSORBSI, SEDIMENTASI) BERBAHAN ARANG BAMBU DALAM PENENTUAN AMBANG BATAS PROSES PENJERNIHAN AIR MINUM THE EFFECT OF VOLUME TO THE ABSORPTION OF FAS SYSTEM (FILTRATION, ABSORPTION, SEDIMENTATION) MADE FROM BAMBOO CARBON IN ORDER TO DETERMINE THE THRESHOLD POINT OF THE DRINKING WATER’S PURIFICATION PROCESS - Puthy Nurlina Sari; Suparno Suparno (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2022)
AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh volume air tanah laboratorium Fisika UNY terhadap efisiensi cahaya, TDS, pH, kadar logam Fe, dan kadar total MPN coliform dalam proses penyaringan menggunakan sistem FAS (Filtrasi, Absorbsi, dan Sedimentasi) Absorben yang digunakan dalam penelitian ini adalah karbon aktif bambu wulung, kerikil aktif Kali Krasak, dan pasir aktif Pantai Indrayanti. Penyaringan dilakukan berulang dengan variasi volume air tanah laboratorium Fisika UNY, Hasil Penelitian menunjukkan bahwa dengan meningkatnya volume air tanah laboratorium Fisika UNY yang diproses melalui sistem FAS maka efisiensi transmisi cahaya yang dihasilkan meningkat hingga 15% kemudian perlahan mengalami penurunan. TDS cenderung menurun hingga selisih 72 ppm, PH seluruh sampel besarnya sama yaitu 6.9, dan kadar logam Fe dalam air mengalami kenaikan sebesar 0.4 mg/L, sedangkan kadar total MPN coliform mengalami penurunan hingga 454 MPN/100 ml meskipun setelahnya kadar total MPN coliform mengalami penurunan secara perlahan.  Kata kunci: Total MPN coliform, Intensitas Transmisi Cahaya, Kadar Fe, dan Karbon Aktif BambuAbstractThis research aimed to know the effect of ground water’s volume obtained from the Yogyakarta State University Physics Laboratory to the light efficiency, Total Dissolve Solid (TDS), pH, concentration of Fe, and total MPN coliform contained on the purification process using FAS (Filtration, Absorption, Sedimentation) Absorbent materials that used on the purification system were Wulung bamboo’s activated carbon, Krasak River’s activated gravel, and Indrayanti Beach’s activated sand. Purification process was repeated with the ground water’s volume variations obtained from the YSU Physics Laboratory, and the result was measured using light transmission instrument with lux meter to determine the water’s transparency, digital TDS meter to determine the total of dissolves solid, digital pH meter to determine the acidity, and the total concentration of Fe and MPN coliform was measured in Yogyakarta Health Agency Laboratory.The result of the research showed that the efficiency of light transmission was increased to 15% within the increased volume of the YSU Physics Laboratory ground water given and slowly reduced, Total Dissolve Solid value was reduced with 72 ppm deviation, 6,9 pH value from all of the sample and increased Fe concentration in the amount of 0,4 mg/L, but MPN coliform concentration was reduced to 454 MPN/100 mL although the total of MPN coliform concentration reduced slowly. Keywords: The large amount of MPN coliform, light transmission intensity, Fe concentration, bamboo activated carbon